Practical tips for starting a successful national postgraduate course [version 4; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Magnus Sundbom (MedEdPublish)
Background Few start national courses, and those that do usually do it once. The aim of this paper is to outline an approach to conduct a successful national postgraduate course. Methods The practical tips were derived from personal experience. Results The 12 tips identified are: define learning needs and curriculum, create a functioning structure, recruit a committed faculty, obtain legitimacy, promote your course, try out the concept, establish administrative support, use modern techniques and accessories, create course-related social activities, keep all on board, collect ongoing evaluation, and stay in control. Conclusion It is hoped that these tips will make it easier for others to take the decisive first step in the exciting task of starting a national course; that is: ‘to know the road ahead - ask those coming back’.